2017
DOI: 10.1007/s13312-017-1146-7
|View full text |Cite
|
Sign up to set email alerts
|

Profile of bullies and victims among urban school-going adolescents in Gujarat

Abstract: We found high prevalence of bullying. The reasons for the same and scope of intervention needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 11 publications
1
25
2
Order By: Relevance
“… 10 The prevalence of peer problems in our population may correlate with 40%–70% prevalence of bullying-related involvement in urban and rural schools around Anand. 11 Rural children were found to be more social. This can be explained based on the effect of urbanisation and preservation of social interactions in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The prevalence of peer problems in our population may correlate with 40%–70% prevalence of bullying-related involvement in urban and rural schools around Anand. 11 Rural children were found to be more social. This can be explained based on the effect of urbanisation and preservation of social interactions in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Patel and coworkers. 25 Students with less number of friends are more likely to be bully perpetrators and victims and the scores on PIPS bully scale and PIPS victim scale are significantly higher in students with less number of friends. This may be due to poor psychosocial adjustment of students involved in any form of bullying similar to previous study conducted by H.A.…”
Section: Discussionmentioning
confidence: 88%
“…Patel and coworkers. 25 There was no significance of academic performance with relation to bully perpetration and victimization in students. Mean scores on each item of PIPS scale is calculated to point the most common bullying behavior is verbal bullying (teasing and making fun) with physical forms not being infrequent, which is similar to earlier studies.…”
Section: Discussionmentioning
confidence: 94%
“…A study in Gujarat in 2017 revealed that overall prevalence of any form of bullying was 49%, with bullies being 29.9% and victims being 29.7%. 12 Another study by Malhi et al 13 also carried out in an Indian sample concluded that the overall prevalence of bullying was 53%, with 19.2% of the population being victims. A recent article published by the Olweus Bullying Prevention Program reported the 2013 trends of Bullying in the US, where 15% of students were victimized and 6% bullied others.…”
Section: Discussionmentioning
confidence: 97%